(untitled) (Annals of Medical Research, 2024)
Aim: To show infusion cannula-associated jet stream effects on the posterior pole of the retina during vitrectomy. Materials and Methods: For this retrospective study 39 eyes of thirty-nine patients were assigned to the two groupsregarding their infusion cannula position during vitrectomy. Group 1 consisted of the patients who had a cannula placed at an angle to the sclera and also there was a two-step entering position of the trocar. Group 2 consisted of the patients who had a cannula that was fixated perpendicular to the sclera. The results of preoperative and postoperative examination of the patients were evaluated. Results: There were 20 patients in group 1 and 19 patients in the group 2. There was no significant difference between the groups regarding preoperative visual acuity (1.79±0.77 logMar for the group 1 and 1.86±0.59 logMar for the group 2, p= 0.989 ). The differences in thepreoperative intraocular pressures (IOPs) were not statistically significant between the groups (13.3±2.9 mmHg for the group 1 and 13.1±2 mmHg for the group 2, p= 0.460). The mean duration of surgery in group 1 was 48±12 minutes and was 50±10 minutes for the group 2 (p= 0.460). The postoperative visual acuity was 0.24±0.21 logMar in group 1 and 0.53±0.28 logMar in group 2. There was statistically significant difference between the groups regarding the postoperative visual acuity (p= 0.0001). The difference of postoperative IOPs were comparable among the groups (14.9±4.2 mmHg for the group 1 and 13.4±2.8 mmHg for the group 2, p= 0.289). Conclusion: The present study shows infusion cannula associated jet stream may reduce postoperative visual acuity. Using new type of design for infusion cannulas or method for placing the infusion cannula in an angle to avoid the flow force on posterior pole should be considered for better vitrectomy results.